Effects of space flight on sperm function and integrity: A systematic review - Ahrari, Khulood; Omolaoye, Temidayo S.; Goswami, Nandu; Alsuwaidi, Hanan; du Plessis, Stefan S. (Frontiers in Physiology, 2022)
With the advancement in space exploration and the intention to establish an inhabitable human settlement on Mars, it is important to investigate the effects of exposure to space/microgravity and the associated radiations on procreation. Sperm function and integrity are fundamental to male reproduction and can potentially be affected by the environmental changes experienced in space. Therefore, this study was conducted to systematically gather, filter, and collate all the relevant information on the effects of spaceflight on male reproductive parameters and functions. A search was performed utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were extracted from the major electronic databases including PubMed, and other credible literature sources. MeSH search terms that were employed included “spermatozoa”, “microgravity”, and “ionizing radiation”. The literature search did not discriminate against papers published before a certain date due to the very limited number of articles available. However, there was a restriction on the male gender and language (English). The parameters included in this study are sperm motility, total sperm count, sperm DNA fragmentation hormonal levels and testicular histology. Following a comprehensive literature search, a total of 273 articles were retrieved and screened, 252 articles were excluded due to the irrelevance to the topic, duplication, and non-original articles. A total of 21 articles met the inclusion criteria and are included in the current study. Findings from these studies showed that sperm motility was decreased after exposure to microgravity and ionizing radiation. Total sperm count was also found to be reduced by microgravity only. Sperm DNA fragmentation was increased by both ionizing radiation and microgravity. Testosterone levels and testicular weight were also decreased by microgravity. Although there is a dearth in the literature regarding the effects of microgravity and ionizing radiation on male reproductive parameters, the available findings showed that exposure to microgravity poses a risk to male reproductive health. Therefore, it is essential to develop countermeasures to either manage, treat, or prevent these consequential adverse effects. Hence, this review also highlights some potential countermeasure approaches that may mitigate the harmful effects of microgravity and associated exposures on male reproductive health.